Foreign Experience In Implementing Hr Management In The Education System: Strategies For Academic Excellence And Organizational Sustainability - Turikova Lazokat Mashrabovna (European International Journal of Pedagogics, 2026)
This article analyzes the stages of development of HR management systems in educational institutions internationally. It also focuses on the "trust-based" models of Finland, the "meritocratic" of Singapore, and the "data-based" models of the United States. The results show that the quality of education is directly related to HR autonomy and the continuous professional development of teaching staff.